Meilensteine, Strassen und das Verkehrsnetz der Provinz Karia - Hild, Friedrich (Denkschriften (Österreichische Akademie der Wissenschaften. Philosophisch-Historische Klasse) ;, 2014)
Milestones are crucial for the scholarly research of roads and the transportation system of a province. Written and archaeological sources as well as the geographic conditions add to the overall picture.